2020
DOI: 10.3389/fcell.2020.518724
|View full text |Cite
|
Sign up to set email alerts
|

Long Non-coding RNA H19 Regulates Porcine Satellite Cell Differentiation Through miR-140-5p/SOX4 and DBN1

Abstract: The H19 gene promotes skeletal muscle differentiation in mice, but the regulatory models and mechanisms of myogenesis regulated by H19 are largely unknown in pigs. Therefore, the regulatory modes of H19 in the differentiation of porcine skeletal muscle satellite cells (PSCs) need to be determined. We observed that H19 gene silencing could decrease the expressions of the myogenin (MYOG) gene, myogenic differentiation (MYOD), and myosin heavy chain (MYHC) in PSCs. Therefore, we constructed and sequenced 12 cDNA … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
13
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 18 publications
(13 citation statements)
references
References 47 publications
0
13
0
Order By: Relevance
“…Results from studies using different cell types support that H19 is mainly, even exclusively, expressed in the cytoplasm 43 45 . Based on this subcellular location, competing endogenous RNA regulation is the most reported mechanism of action of H19, followed by direct binding to transcription regulators or other proteins 46 , 47 .…”
Section: Discussionmentioning
confidence: 87%
“…Results from studies using different cell types support that H19 is mainly, even exclusively, expressed in the cytoplasm 43 45 . Based on this subcellular location, competing endogenous RNA regulation is the most reported mechanism of action of H19, followed by direct binding to transcription regulators or other proteins 46 , 47 .…”
Section: Discussionmentioning
confidence: 87%
“…An increasing number of studies have reported an association between lncRNAs and cSCC ( 27 ). Accumulating evidence has revealed that H19, as a cancer-related lncRNA, served an important role in physiological activities and pathological mechanisms ( 16 , 28 , 29 ). For example, H19 was reported to act as an oncogene in bladder, gastric, breast and thyroid cancer, in addition to glioma ( 15 , 30 33 ).…”
Section: Discussionmentioning
confidence: 99%
“…H19 , a well-known imprinted lncRNA [ 9 ], is expressed in animal skeletal muscle and heart tissues and exerts important functions [ 10 ]. H19 can inhibit insulin-like growth factor 2 ( IGF2) transcription by binding to polycomb repressive complex 2 (PRC2) [ 11 ] and recruit TAR DNA-binding protein 43 (TDP43) and drebrin 1 (DBN1) to induce differentiation of PSCs [ 12 , 13 ]. The lncRNA metastasis-associated lung adenocarcinoma transcript 1 ( Malat1) functions via the suppressor of variation 39 homolog 1 (Suv39h1) to repress the expression of the target gene myogenic differentiation factor ( MyoD) [ 14 ].…”
Section: Introductionmentioning
confidence: 99%